2007
DOI: 10.1038/sj.emboj.7601951
|View full text |Cite
|
Sign up to set email alerts
|

Parallel topology of genetically fused EmrE homodimers

Abstract: EmrE is a small H þ -coupled multidrug transporter in Escherichia coli. Claims have been made for an antiparallel topology of this homodimeric protein. However, our own biochemical studies performed with detergent-solubilized purified protein support a parallel topology of the protomers. We developed an alternative approach to constrain the relative topology of the protomers within the dimer so that their activity can be assayed also in vivo before biochemical handling. Tandem EmrE was built with two identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…minus of the first to N terminus of the second monomer (tail to head). This was achieved by means of defined linkers that are not compatible with an antiparallel topology either because they are too hydrophilic or too short (9). In these studies we showed that all the constructs are functional in vivo because they confer resistance to EmrE substrates, and they catalyze energy-dependent ethidium efflux.…”
Section: Forcing a Homodimer With Identical Protomers Into An Antiparmentioning
confidence: 98%
See 2 more Smart Citations
“…minus of the first to N terminus of the second monomer (tail to head). This was achieved by means of defined linkers that are not compatible with an antiparallel topology either because they are too hydrophilic or too short (9). In these studies we showed that all the constructs are functional in vivo because they confer resistance to EmrE substrates, and they catalyze energy-dependent ethidium efflux.…”
Section: Forcing a Homodimer With Identical Protomers Into An Antiparmentioning
confidence: 98%
“…The segment inserted was based on the sequence of a mutant of human glycophorin A (GpA) that does not dimerize (28). Such a fusion, with an odd number of TMs, would have the N and C termini at opposite sides of the membrane, contrasting with the previously generated eight TM proteins with hydrophilic linkers of variable length (9). Fusions with several sequences of GpA and several linkers were constructed (supplemental Table S1), and they all yielded functional proteins.…”
Section: Forcing a Homodimer With Identical Protomers Into An Antiparmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the design and construction of functional EmrE chimeras where monomers are linked by short polar loops not favored energetically to cross the bilayer (20). Furthermore, residues predicted to be on opposite sides of the membrane in the antiparallel dimer model can be cross-linked without significant perturbation of transport (21).…”
mentioning
confidence: 99%
“…The structure and topology of the homodimeric carrier protein remained controversial (Ninio et al, 2004;McHaourab et al, 2008;Steiner-Mordoch et al, 2008;Korkhov et al, 2009;Henzler-Wildman, 2012) until a joint NMR and single-molecule FRET investigation has recently revealed an asymmetric antiparallel arrangement with inward-and outward-facing subunits related by a pseudo-twofold symmetry axis parallel to the membrane plane (Morrison et al, 2012). Furthermore, solid state NMR and cryo-EM have demonstrated asymmetry at the ligand-binding pocket (Lehner et al, 2008), whereas spin labelling and EPR have revealed asymmetry in the TM helices .…”
Section: E Primary and Secondary Transportersmentioning
confidence: 99%